Impact of restrictions on the COVID-19 pandemic situation in Poland - Sergiusz Herman (Statistics in Transition new series (SiTns), 2022)
The COVID-19 pandemic has had a substantial impact on public health all over the world. In order to prevent the spread of the virus, the majority of countries introduced restrictions which entailed considerable economic and social costs. The main goal of the article is to study how the lockdown introduced in Poland affected the spread of the pandemic in the country. The study used synthetic control method to this end. The analysis was carried on the basis of data from the Local Data Bank and a government website on the state of the epidemic in Poland. The results indicated that the lockdown significantly curbed the spread of the COVID-19 pandemic in Poland. Restrictions led to the substantial drop in infections - by 9500 cases - in three weeks. The results seem to stay the same despite the change of assumptions in the study. Such conclusion can be drawn from the performance of the placebo-in-space and placebo-in-time analyses.
Keywords: 519; COVID-19; coronavirus; lockdown; synthetic control method; treatment effect